2009
DOI: 10.1186/1471-2458-9-379
|View full text |Cite
|
Sign up to set email alerts
|

Health-promoting lifestyles of university students in Mainland China

Abstract: Background: Health-promoting lifestyles of adolescents are closely related to their current and subsequent health status. However, few studies in mainland China have examined health-promoting behaviors among university students, notwithstanding the dramatic development of higher education over the past two decades. Moreover, no study has applied a standardized scale to such an investigation. The adolescent health promotion (AHP) scale has been developed and is commonly used for measuring adolescent health-prom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

18
100
4
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 99 publications
(123 citation statements)
references
References 26 publications
18
100
4
1
Order By: Relevance
“…The finding that Chinese participants had significantly less frequent participation in physical activity compared to the Western group is consistent with previous research demonstrating a general lack of exercising among some Asian communities (ABS, 2007;Wang et al, 2009). Wang et al (2009) have identified factors such as lack of exercise facilities, heavy schoolwork demand, and the popularization of computers and the Internet as reducing young people's interest in participating in physical activities.…”
Section: Discussionsupporting
confidence: 80%
See 3 more Smart Citations
“…The finding that Chinese participants had significantly less frequent participation in physical activity compared to the Western group is consistent with previous research demonstrating a general lack of exercising among some Asian communities (ABS, 2007;Wang et al, 2009). Wang et al (2009) have identified factors such as lack of exercise facilities, heavy schoolwork demand, and the popularization of computers and the Internet as reducing young people's interest in participating in physical activities.…”
Section: Discussionsupporting
confidence: 80%
“…Wang et al (2009) have identified factors such as lack of exercise facilities, heavy schoolwork demand, and the popularization of computers and the Internet as reducing young people's interest in participating in physical activities.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…1 Adopting healthy behaviors and lifestyle involves not only knowledge on the subject, but also the learning and development of emotional, cognitive and behavioral competencies so that such technical and theoretical knowledge can be put to practice in different real life contexts. 2 Knowledge on healthy lifestyle in adolescence has become an important research topic 3 and many studies have used the Adolescent Health Promotion Scale (AHPS). Notwithstanding, there is an absence of studies in the Portuguese language or in Portugal.…”
Section: Introductionmentioning
confidence: 99%